Um estudo da relação entre diversidade e competitividade nas empresas - Nóbrega, Bruno Andrade (2009)
This dissertation aims to investigate how the present diversity in the workforce can contribute to increasing the competitiveness in the company. The central problem was how the diversity in the workforce contributes to business competitiveness? The basic theoretical reference was about diversity and competitiveness, including subjects as identity, creativity and innovation. The methodology used was qualitative research to allow greater analysis about the subject, allowing a greater perception about the feelings of those who took the primary source of data for this research. For data collection was chosen for conducting in-depth interviews - guided by a semistructured script. The results showed that diversity exists in varying degrees in business, however, the existence of diversity in business should be more random and / or compliance with the Decree 3298, 20 December 1999 than a policy of social inclusion.